Effect of metabolic clearance rate and hepatic extraction of insulin on hepatic and peripheral contributions to hypoglycemia. - Chap, Z (1985)
Effects of alterations in metabolic clearance rates, hepatic extraction, and plasma concentrations of insulin on hepatic and peripheral contribution to hypoglycemia and glucose counterregulation were studied in conscious dogs. Since insulin and sulfated insulin had markedly different metabolic clearance rates (34 +/- 1 vs. 16 +/- 1 ml/kg per min, respectively) and fractional hepatic extraction (42 +/- 1% vs. 15 +/- 2%, respectively), biologically equivalent amounts infused intraportally produced twofold higher hepatic vein and artery sulphated insulin concentrations and concentrations that were 30% higher in the portal vein. This significantly larger arterial/portal concentration ratio (0.67 vs. 0.45, respectively) permitted assessment of differential distribution of insulin on glucose turnover using [3-3H]glucose. Insulin and sulfated insulin (1 and 2 mU/kg per min) caused similar hypoglycemia. While insulin transiently suppressed glucose production and increased glucose disappearance, sulfated insulin had significantly greater effects on glucose disappearance and clearance, without suppression of glucose production. Despite similar hypoglycemia, sulfated insulin caused greater increment in glucagon. 3 mU/kg per min insulin caused more rapid and greater hypoglycemia, greater glucose clearance, and greater glucagon increments without suppression of glucose production, which indicates that with larger doses of insulin counterregulation can absolutely mask the suppressive effect of insulin. The effects of insulin and sulfated insulin were evaluated using euglycemic clamp to eliminate interference from stimulated counterregulation. Sequential infusion of 1 and 2 mU/kg per min of both insulins suppressed endogenous glucose production to 0 at 150 min, which indicates that the apparent lack of a hepatic effect of sulfated insulin during hypoglycemia was masked by greater counterregulation. This greater counterregulation may reflect greater peripheral glucose clearance, and prevented greater hypoglycemia than after the same insulin doses. The results indicate that the different rates of removal and the total metabolic clearance rate caused different concentrations and relative distribution between the portal and arterial blood compartments, leading to the significantly different contributions by the liver and peripheral tissues to the same hypoglycemia.